A Free-Floating Technique Simplifies Lower Face Thread Lift for Premature Lower Face Aging: An Evidence-Based Case Report - Mandagie, Aprilia Karen; Sutanto, Eviana Budiartanti; Wibowo, Devina Karen; Susianto, Indra Adi (Medica Hospitalia : Journal of Clinical Medicine, 2026)
INTRODUCTION: Skin aging is a complex biological process influenced by a combination of endogenous (intrinsic) and exogenous (extrinsic) factors. A Thread Lift is a cosmetic procedure that lifts and tightens sagging tissue while enhancing facial contours, using threads made from the same material utilized in surgical wound closure. This case report aims to present a new, simplified thread lift technique available to dermatologists today, covering preventive measures, cosmetic strategies, topical and systemic therapeutic agents, and invasive procedures. CASE: A 40-years-old man, a contractor and heavy smoker who participates in outdoor sports, is frequently exposed to the sun. He has complained of sagging in the lower cheek area for the past year. A thread lift treatment was performed. On the patient's second visit, a thread lift was conducted after marking an anchoring pattern in the retaining ligament and injecting 2% lidocaine at the entry point of the lateral face area. This was followed by tumescent anesthesia using a 25G cannula along the thread lift marking. The entry point was opened using an 18G needle, and the bevel-down thread lift was inserted above the mandibular angle into the subcutaneous layer without injuring the facial muscles as per the marking. The thread lift protocol used a thread (thread 6D cog PDO threads with needles). After the thread lift is inserted into the marionette line, pull on the entry point slowly until the thread lift elevates the epidermis to the subcutaneous layer, achieving repositioning of the lower face. CONCLUSION: The free-floating Thread lift technique is an aesthetic procedure with a quick healing process and minimal side effects that help prevent premature aging, making it simple and suitable for all dermatologists to perform.